EXPLORING THE POTENTIAL OF RENDANG TO BE PROMOTED AS THE LOCAL FOOD HERITAGE PRODUCT FOR TOURISM IN NEGERI SEMBILAN - Mohd Farudz, Baiduri Zaiyyanna; Abd Rahman, Nur Hidayah; Md Sawari, Siti Salwa (2022)
Rendang is a popular Malay heritage dish found across Nusantara, which includes Malaysia and Indonesia. However, Indonesian researchers have dominated most of Rendang studies, particularly those focusing on Rendang's characteristics, such as knowledge, preparation method, sensory attributes, history, and cultural significance. This fundamental characteristic is necessary for the preservation and promotion of Rendang as a tourism product based on this fundamental concern. The purpose of this research is to explore the potential of Rendang to be promoted as a local food heritage product for tourism in Negeri Sembilan, Malaysia. The qualitative study has been implemented through semi-structured interview questions. A total of seven respondents took part in this investigation. Thematic analysis was used to examine the data. The findings of this study are focused on the characteristics of Rendang, which include three aspects: food heritage knowledge, sensory attributes, and Rendang's cultural values. In particular, this study found Rendang's history can be traced back to the Sumatran migration to Negeri Sembilan. However, there are two types of Rendang in Negeri Sembilan: Rendang Cili Padi or Rendang Kuning (yellow-colored) and Rendang Hitam (black-colored). Each type of rendang uses different ingredients, but they are commonly cooked until they are completely dry. Both types of Rendang had a robust flavour, a fragrant aroma, a lovely texture, and a black and yellow colour. The participants believed that heritage foods should be marketed to people from other cultures. So, this research is important for promoting Rendang as a traditional cuisine heritage of Negeri Sembilan to promote its culinary tourism as one of Malaysia's gastronomic tourism attractions.